(untitled) (American Journal of Research in Humanities and Social Sciences, 2023)
This article is about the traditional national dress of the Tashkent region, such as the Ancient state of Ilak (modern Okhangaron district, the cities of Angren and Almalyk) of the peoples of the Syrdarya (Akkurgan district) and the territory of the Bostanlyk district. In this article we can also learn about the color palettes of fabrics that were used in the clothes of this people